Pengaruh Dana Bansos Umkm Terhadap Peningkatan Perekonomian dalam Masyarakat di Kota Medan - Noni Rozaini; Aulia Nurfitriana (Pusat Riset dan Inovasi Nasional, 2023)
This analytical research was conducted with the aim of knowing the Effect of Social Assistance Funds for Micro, Small and Medium Enterprises on Increasing the Economy in North Sumatra Province, especially Medan City in 2011 – 2018. In this study the variable used is the Economy (GDP) as the dependent variable. Then the independent variables are the Human Development Index (IPM), and the Development of Inflation (Inflation). The data source used in this study is secondary data with data for the period 2011-2018. Data obtained from the Central Bureau of Statistics (BPS) of North Sumatra Province. This type of research is using quantitative research and the analytical technique used in this research is Multiple Linear Regression Analysis. This analysis also uses E-Views 9. The results of the study show that HDI and inflation have a significant and positive effect on economic development (GDP) in Medan City.